1985
DOI: 10.1073/pnas.82.22.7748
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial expression of the acquired immunodeficiency syndrome retrovirus p24 gag protein and its use as a diagnostic reagent.

Abstract: A retrovirus [lymphoadenopathy-associated virus, human T-cell leukemia virus type III, acquired immunodeficiency syndrome (AIDS)-related virus] suspected of causing AIDS has been isolated recently. The detection of exposure to this retrovirus in donors of various blood products is important to prevent transmission of the disease from these donors to recipients. In the majority of cases, the detection of antibodies directed against either the viral core protein, a Mr approximately equal to 24,000 protein termed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The FIV ELISA uses recombinant gag proteins that are believed to be highly immunogenic, yet conserved among feline lentiviruses. 9,12 Overall, there was 83% agreement (20/24) between the two forms of antibody testing, with only four discrepant results (Table 1). All four of the discrepant results were positive when using the FIV ELISA and negative when using the FIVpco ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…The FIV ELISA uses recombinant gag proteins that are believed to be highly immunogenic, yet conserved among feline lentiviruses. 9,12 Overall, there was 83% agreement (20/24) between the two forms of antibody testing, with only four discrepant results (Table 1). All four of the discrepant results were positive when using the FIV ELISA and negative when using the FIVpco ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…Receptor binding of human complement fragment C5a (Mandecki et al, 1985) and biological activity of FMDV proteinase (Klump et al, 1984) were demonstrated using unpurified lysis supernatants. Pure retroviral p24 gag protein was purified from E. coli in a single immunopurification step (Dowbenko et al, 1985) while a five-step process was used to produce human growth hormone (Olsen et al, 1981). Other examples of soluble proteins are human IFN-a (Staehelin et al, 1981;De Maeyer et al, 1982) boVine IFN-a (Grosfeld et al, 1985), chicken triosephosphate isomerase (Straus & Gilbert, 1985), human lymphotoxin (Gray et al, 1984), human TNF (Pennica et al, 1984) and murine TNF .…”
Section: Direct Expressionmentioning
confidence: 99%
“…These assays used the solid phase coated with viral antigens and polyclonal antibodies to human immunoglobulins conjugated to an enzyme for detection of HIV-specific antibodies (1,24). The second-generation assays used HIV recombinant antigens instead of viral lysate as the source of antigen on the solid phase and also incorporated recombinant antigen for HIV-2 (6,10,11,12,13,16). These assays had improved specificity though the overall sensitivity remained similar to that of the first-generation assays.…”
mentioning
confidence: 99%